Inclusive Policy and Performance of Women Representatives in Central Alignment of local level of in Nepal - Kuikel, Shachita (Rural Development Journal, 2024)
This paper is dealing Inclusive policy as one of the beauties of inclusive democracy through affirmative action to ensure gender equality in this era. It significantly tries to recognize women as one of the backward cluster in the society and how they are working in sectorial diversities at local level as a representatives of people. For ensuring equal access to decision making process, women’s inclusive participation at local level is means to strengthen root to democracy. This paper tries to deal with the role of policy to enhance performance of women representatives through secondary and primary data.